Predporodna in poporodna obravnava žensk v Sloveniji - Jug Došler, Anita (Obzornik zdravstvene nege, 2023)
Introduction: In this paper we present the results of the study on preventive activities for the protection of women's reproductive health in Slovenia in the prenatal and postpartum period. The aim of the research was to study the frequency and content of prenatal and postnatal care of women in Slovenia. Methods:. A cross-sectional study was conducted from March 2015 to March 2022. Data were collected using a questionnaire based on a random sample of 2,102 women. Data analysis included basic descriptive statistics with calculations of frequencies and percentages. To analyze the differences between primiparous women and multiparous women, the Chi square test was used. Statistical significance was considered at the 5% risk level.Results: The survey showed that visits by community nurses during pregnancy were very rare (14%). According to women's assessments, the most frequent content of the visit was providing instructions to pregnant women regarding conditions under which they should immediately go to the maternity hospital (61%). After labour, most mothers (22%) and their newborns received four visits from a community nurse. After delivery, women were most often counselled about breastfeeding and the benefits of breastfeeding and breast milk for the baby (79%), while the most common form of care for the newborn was bathing (92%).Discussion and conclusion: The results show that in Slovenia, the frequency and content of visits by a community nurse or midwife paid to pregnant and postpartum women vary. Visits of postpartum women focus more often on the newborn, as shown by the list of the three most frequent interventions during postpartum visits: counselling on the benefits of breastfeeding, breastfeeding positions, and nutrition while breastfeeding).
Keywords: babice; community health care; medicinske sestre; midwifes; newborns; nosečnost; novorojenčki; nurses; patronaža; patronažno varstvo; porod; pregnancy